HLA antigens in Italian patients with primary Sjögren's syndrome. Issue 5 (May 1986) - Vitali, C; Tavoni, A; Rizzo, G; Neri, R; D'Ascanio, A; Cristofani, R; Bombardieri, S
Abstract : Twenty eight Italian patients with primary Sjögren's syndrome were typed for class I and class II alloantigens of the major histocompatibility complex. Patients with Sjögren's syndrome had higher prevalence of DR3 (46.4% v 14% in the control population, p corrected less than 0.02), while similar prevalence was found for DR2 and DRw52 alloantigens. DR3 correlated with DRw52 (p less than 0.0001), anti-Ro(SSA) (p less than 0.0002) and anti-La(SSB) (p less than 0.02) antibodies, and extraglandular manifestations (p less than 0.02). In addition, extraglandular involvement was associated with anti-Ro antibodies (p less than 0.05) and raised gammaglobulins (p less than 0.02). In Italian patients with primary Sjögren's syndrome DR3 is the genetic marker related to this clinical entity and seems to identify a disease subset characterised by autoantibody production and extraglandular manifestations.